Workplace Accidents and Work-related Illnesses of Household Waste Collectors - Byung Yong Jeong; Sangbok Lee; Jae Deuk Lee (Elsevier, 2016)
Background: Household waste collectors (HWCs) are exposed to hazardous conditions. This study investigates the patterns of workplace injuries and work-related illnesses of HWCs. Methods: This study uses cases of workplace injuries and work-related illnesses of HWCs that occurred between 2010 and 2011. We analyzed 325 cases of injuries and 36 cases of illnesses according to the workers' age, length of employment, size of workplace, injured part of body, day and month of injury, type of accident, agency of accident, and collection process. Results: There were significant differences in the effect of workers' length of employment, injured part of body, type of accident, agency of accident, and collection process. Results show that most injuries occur in workers in their 50s and older. This study also shows that 51.4% of injuries occur at businesses with 49 employees or fewer. Injuries to waste collectors happen most often when workers are electrocuted after slipping on the ground. The second most prevalent form of injury is falling, which usually happens when workers hang from the rear of the truck during transportation or otherwise slip and fall from the truck. Work-related illnesses amongst waste collectors are mostly musculoskeletal conditions due to damaging postures. Conclusion: These findings will be instructive in devising policies and guidelines for preventing workplace injuries and work-related illnesses of HWCs.